The acceptance and usability of educational videos on falls in older people for online clinical education: a usability study among clinical undergraduates in Malaysia - Sumaiyah Mat; Deepashini Harithasan; Normala Mesbah; Devinder Kaur Ajit Singh; Hern, Jia Lin; Toh, Wu Shern; Lee, Shan Xian; Law, Zen Zan; Chua, Qi Qi; Abby Dania Danny; Asfarina Zanudin; Mohd Azzuan Ahmad; et al. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Educational videos and other multimedia materials are frequently employed to enhance clinical undergraduate learning. The acceptability and use of a fall prevention training videos by Malaysian clinical students are examined in this study. The use of multimedia in the classroom offers numerous advantages, but it is important to understand the needs, preferences, and feedback of the students regarding its usefulness and efficacy. Therefore, the objective of this study is to evaluate the acceptability and usability of the fall prevention instructional videos among clinical undergraduates in Malaysia through quantitative and qualitative study methods. This study looks at the acceptability and usage of fall prevention videos among clinical undergraduates in Malaysia. A quantitative and qualitative study of 53 clinical undergraduate students in Malaysia was conducted. The System Usability Scale (SUS) was adapted for our study to incorporate two open-ended questions regarding educational video continuity and practicality, feedback sections, and closed-ended questions addressing video flaws. The educational video on fall prevention has an excellent usability score of 73.26 ± 13.32. Most of the feedback suggested trimming the videos because 15 participants (28 %) felt it was too long. Many participants said that the educational videos were essential for practical sessions and future learning. The consensus was that educational videos should be kept up to date for future learning and usefulness, but more improvements are required to make the learning process better for the students.